A Framework for Visual Modular Design of Educational Operating System - Al-Oudat, Naeem (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Operating systems are a vital part in most computing systems. However, learning basic concepts of operating systems are hard for normal students although they are necessary and important. State of the art in teaching operating systems depends on studying existing open source operating systems like Linux, hacking teaching operating systems like Xv6, or using simulators. Difficulties of learning still there in these methods, since they require a great deal of system programming techniques. In this paper, we propose a novel direction in learning operating systems that is solely dependent on visually building the operating system. By using this method, we mitigated the complexity of going into system programming details. The development platform consists of key building blocks that a user can drag and drop into a working panel to build his own operating system. Then, the user can compile and run his own-built system on a virtual machine or any Intel architecture hardware. This paper provides the framework’s key points for building an operating system by modules. It also discussed a simple prototype as a proof of the concept.